2018
DOI: 10.1002/ajmg.a.60686
|View full text |Cite
|
Sign up to set email alerts
|

Terminal osseous dysplasia with pigmentary defects (TODPD) in a Turkish girl with new skin findings

Abstract: Terminal osseous dysplasia with pigmentary defects (TODPD; MIM #300244) is an extremely rare, X-linked dominant, in utero male-lethal disease, characterized by skeletal dysplasia of the limbs, pigmentary defects of the skin, and recurrent digital fibromatosis of childhood. Delayed/ abnormal ossification of bones of the hands and feet, joint contractures, and dysmorphic facial features may accompany. A single recurrent mutation (c.5217 G>A) of the FLNA gene which causes cryptic splicing was identified as the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…5 These conditions suggested that FLNA may modulate the activity of transforming growth factor-b, which in turn regulates the expression of elastin. 3 However, Azakli et al 10 reported that a biopsy obtained from an alopecic area of a scalp revealed elastic fibers within the dermis that were of normal shape and number. Similarly, in our case, Verhoeff-Van Gieson staining of the two biopsies from the atrophic macule on the forehead and digital fibroma both revealed normal elastic fibers in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…5 These conditions suggested that FLNA may modulate the activity of transforming growth factor-b, which in turn regulates the expression of elastin. 3 However, Azakli et al 10 reported that a biopsy obtained from an alopecic area of a scalp revealed elastic fibers within the dermis that were of normal shape and number. Similarly, in our case, Verhoeff-Van Gieson staining of the two biopsies from the atrophic macule on the forehead and digital fibroma both revealed normal elastic fibers in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…FLNA is a F-actin cross-linking protein and acts as a scaffold for a wide range of molecules, including intracellular signaling molecules, adhesion molecules, ion channels and transcription factors ( Stossel et al, 2001 ; Popowicz et al, 2006 ; Zhou et al, 2007 ; Nakamura et al, 2011 ). FLNA mutations related to various human diseases including peri-ventricular nodular heterotopia, familial cardiac valvular dystrophy, skeletal dysplasias and thrombocytopenia ( Nurden et al, 2011 ; Clapham et al, 2012 ; van der Werf et al, 2013 ; Fernández et al, 2018 ; Azakli et al, 2019 ; Toomer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%